2012
DOI: 10.1097/prs.0b013e3182547d09
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Stability and Flap Complications after Deep Inferior Epigastric Perforator Flap Breast Reconstruction

Abstract: Increasing body mass index predisposes patients to delayed wound healing complications in both flap and donor-site locations. Nevertheless, overall flap complications remain similar across all body mass index groups. Abdominal wall stability was maintained. Given a similar flap complication profile and maintenance of abdominal stability, DIEP flaps are recommended in patients with increased body mass index. CLINICAL QUESTION/LEVEL OF EVDENCE: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…The result was consistent with the reported literature [24, 41]. The incidence of wound dehiscence was more common with a rate of 6% (95% CI: 4%–9%), which was almost equal to the DIEP flap [47, 48] (Knox ADC et al reported that the rate was 6%, and Ochoa O et al reported that the rate was 6.2%) and less than the TUG flap [17] (Schoeller T et al indicated that the rate was 7.3%). Just as the literature reported, maybe a semicircular incision or postoperative supine position or sitting position disturbed normal wound healing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result was consistent with the reported literature [24, 41]. The incidence of wound dehiscence was more common with a rate of 6% (95% CI: 4%–9%), which was almost equal to the DIEP flap [47, 48] (Knox ADC et al reported that the rate was 6%, and Ochoa O et al reported that the rate was 6.2%) and less than the TUG flap [17] (Schoeller T et al indicated that the rate was 7.3%). Just as the literature reported, maybe a semicircular incision or postoperative supine position or sitting position disturbed normal wound healing.…”
Section: Discussionsupporting
confidence: 91%
“…Various complications were summarized in Table 2. The result was almost equal to that of the DIEP flap (Ochoa O et al reported that the rate of DIEP was 23.8% [48]) and less than muscle-sparing transverse rectus abdominis myocutaneous (MS-TRAM) or superficial inferior epigastric artery (SIEA, Wang X-L et al reported that the rates of MS-TRAM and SIEA were 25.6% and 26.7%, respectively [49]). Thirdly, almost all included studies showed a satisfactory aesthetic outcome of the donor site, such as minimal contour deformity or invisible incision scar [24, 27, 34, 41].…”
Section: Discussionmentioning
confidence: 95%
“…First, Chang et al observed significantly higher rates of complications in overweight and obese patients having a breast reconstruction with free TRAM flaps [1]. Besides higher frequencies of lower abdominal bulging and herniation due to increased intraabdominal pressure in overweight patients [17,18], several studies confirmed a significantly higher overall risk for complications after reconstructions with abdominal based free flaps [3,4,[19][20][21][22][23]. As an example, Boczar et al [4] observed a reoperation rate of about 40% in obese patients and severe wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…The success of a DIEP flap-based breast reconstruction depends on several factors; For instance, the perfusion of transferred flap is the most important factor that determines postoperative complications. Standards of perfusion monitoring of DIEP-flap should be carried out by observing temperature, vascular pulse, vessel diameter correlation, capillary response prior to surgical intervention (7,14,(20)(21)(22). To decrease the overall complication rate, it is necessary to understand the "dynamics and anatomy of blood flow" through the deep and superior inferior epigastric systems (7).…”
Section: Preoperative Periodmentioning
confidence: 99%